Method for coating mica with titanium dioxide
By covering titanium dioxide on mica, the safety hazards of nanomaterials penetrating the skin in traditional children's sunscreens are solved, and effective ultraviolet protection and gentleness to children's skin are achieved.
Patent Information
- Application Number
- CN202411916153.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-24
- Publication Date
- 2025-03-28
AI Technical Summary
Traditional children's sunscreens use a large amount of nanomaterials, which poses a safety hazard that nanoparticles may penetrate children's skin barriers.
By coating titanium dioxide on mica, large particles are formed to avoid the potential risks of nanoparticles, and by strictly controlling reaction conditions and washing steps, ensuring the appropriate pH of the product and reducing irritation to children's skin.
It achieves safety to prevent nanoparticles from penetrating the skin, provides effective UV protection, and reduces irritation to children's skin.
Smart Images

Figure BDA0005206865390000081 
Figure BDA0005206865390000091
Abstract
Description
Technical Field
[0001] The present application relates to the field of sunscreen skin care products, and more specifically, to a method for coating titanium dioxide on mica. Background Art
[0002] The ultraviolet rays emitted by the sun include UVA, UVB and UVC. Most of the UVC is absorbed by the ozone layer, and the ones that reach the ground are mainly UVA and UVB. UVB can cause sunburn, erythema, blisters and other symptoms; UVA can cause skin tanning and aging, and long-term exposure may increase the risk of skin cancer. Therefore, people usually use sunscreen to avoid UV damage to the skin.
[0003] Early sunscreen products were mainly physical sunscreens, using simple mineral powders such as zinc oxide to apply to the skin. However, these products have a rough texture, poor feel, and limited sunscreen effect. Modern sunscreens pay more attention to comprehensive performance, requiring not only efficient sunscreen effects, but also product safety, stability, comfort, etc. Children's skin is thinner and more delicate than adults, the stratum corneum has not yet fully matured, and the skin barrier function is relatively weak. This makes children's skin less resistant to ultraviolet rays and more susceptible to damage from ultraviolet rays. Therefore, sunscreens for children should pay more attention to safety and mildness while ensuring sunscreen effects.
[0004] Existing sunscreens use a lot of nanomaterials, but because the nanoparticles are extremely small, usually less than 100nm, children's skin is thinner and more delicate than adults', the stratum corneum has not yet fully matured, and the skin barrier function is relatively weak. These nanoparticles may penetrate the children's skin barrier and enter the human body, posing a safety hazard in children's long-term use. Summary of the invention
[0005] In order to solve the above problems, the present application provides a method for coating titanium dioxide on mica.
[0006] The present application provides a method for coating titanium dioxide on mica using the following technical solution: A method for coating titanium dioxide on mica comprises the following steps: Add 60-70 parts of mica by weight to 1000-1200 parts of water, stir to form a suspension, then add 30-40 parts of titanium dioxide to the suspension and stir to obtain a mixed solution; Add dilute hydrochloric acid solution to the mixed solution to adjust the pH of the mixed solution to 2-2.5; raise the temperature of the mixed solution to 45-80°C and reflux for 2h; After the reaction is completed, the mixed solution is cooled to room temperature, filtered and washed until the pH is 5-7; The washed product is placed in an oven for drying to obtain mica with titanium dioxide coated on the surface.
[0007] By adopting the above technical scheme, a large amount of nanomaterials are used in traditional sunscreens, and there is a safety hazard that nanoparticles may penetrate the skin barrier of children and enter the human body. The present application scheme forms relatively large particles by coating titanium dioxide on mica, which will not produce the potential risk of nanoparticles and is particularly suitable for children. The mica in the material itself is stable in nature and is relatively gentle on children's delicate skin. At the same time, during the preparation process, by strictly controlling the reaction conditions and washing steps, the pH of the final product is ensured to be within the range suitable for children's skin, reducing irritation to children's skin. By adding a dilute hydrochloric acid solution to adjust the pH of the mixed solution to 2-2.5, and raising the temperature of the mixed solution to 45-80°C for reflux reaction for 2 hours, the uniform coating of titanium dioxide on the mica surface can be ensured, thereby improving the quality and performance of the product. Titanium dioxide has excellent ultraviolet reflection and scattering capabilities. By coating titanium dioxide on mica, the sunscreen effect of titanium dioxide can be fully exerted to provide effective ultraviolet protection for children.
[0008] Optionally, the following steps are also included: Add 60-70 parts of mica by weight to 1000-1200 parts of water, stir to form a suspension, add 20-30 parts of sodium alginate to the suspension, stir for 10-15 minutes, then add 30-40 parts of titanium dioxide to the suspension and stir to obtain a mixed solution; Add dilute hydrochloric acid solution to the mixed solution to adjust the pH of the mixed solution to 2-2.5; raise the temperature of the mixed solution to 45-80°C and reflux for 2h; After the reaction is completed, the mixed solution is cooled to room temperature, filtered and washed until the pH is 5-7; The washed product is placed in an oven for drying to obtain mica with titanium dioxide coated on the surface.
[0009] By adopting the above technical solution, mica is made into a suspension so that it is evenly dispersed in water. After adding sodium alginate, the sodium alginate molecules will be adsorbed on the surface of mica. Sodium alginate is a polysaccharide with rich functional groups (such as carboxyl and hydroxyl groups), which can bind to the surface of mica through interactions such as hydrogen bonds. When titanium dioxide is added later, sodium alginate plays a bridge role between mica and titanium dioxide. It can guide titanium dioxide to be more evenly distributed on the surface of mica, making the coating of titanium dioxide more uniform. Compared with the method without adding sodium alginate, the local agglomeration of titanium dioxide that may occur is avoided, thereby improving the consistency of product quality and performance. After adjusting the pH and heating the reflux reaction, the presence of sodium alginate can prevent the coated titanium dioxide from falling off to a certain extent. This is like adding a layer of "adhesive" between the coating layer and the mica, making the coating structure more firm and improving the stability of the product during actual use. And sodium alginate can adjust the rheological properties of the mixed solution to make the entire reaction system more stable. During the stirring process, it can prevent the rapid sedimentation of particles and keep the particles well dispersed in the solution.
[0010] Optionally, the mica includes one of sericite, muscovite, and synthetic fluorphlogopite.
[0011] By adopting the above technical solutions, sericite has a fine flaky structure, which can increase the smoothness and skin-fitting property of the product. Its flaky structure can form a good physical barrier and enhance the reflection and scattering effect of ultraviolet rays. Sericite has high chemical stability and is not easy to react chemically with other ingredients, which ensures the stability of the product during storage and use. At the same time, it is less irritating to the skin and is suitable for children's sensitive skin. Muscovite has good insulation properties, which can reduce the impact of external factors on sunscreen ingredients and ensure the sunscreen effect of titanium dioxide. Synthetic fluorphlogopite has a high refractive index and ultraviolet reflection ability, which can enhance the sunscreen effect. At the same time, the surface of synthetic fluorphlogopite is smooth and easy to disperse in the product, improving the uniformity and stability of the product.
[0012] Optionally, the titanium dioxide includes one of rutile titanium dioxide or anatase titanium dioxide.
[0013] By adopting the above technical solution, the refractive index of rutile titanium dioxide is about 2.71, which is higher than that of anatase titanium dioxide. It can more effectively reflect and scatter ultraviolet rays, providing stronger sun protection for children. It is not easy to undergo chemical changes under high temperature, light and other conditions, and can maintain the stability of sunscreen performance. The whiteness of anatase titanium dioxide is usually higher than that of rutile titanium dioxide, which can make sunscreen products have a better appearance. In the production process, the preparation process of anatase titanium dioxide is relatively simple and the cost is low.
[0014] Optionally, the particle size of the titanium dioxide is 30-200 nm.
[0015] By adopting the above technical solution, the smaller particle size makes the particles have a larger specific surface area, which can fully contact with ultraviolet rays and reflect them back, thereby providing a good sun protection effect. Under different lighting conditions, it can maintain a good ultraviolet reflection ability and will not show performance degradation due to long-term exposure to sunlight.
[0016] Optionally, the mica is further subjected to an acidification pretreatment before preparing the suspension, and the acidification pretreatment comprises: Add mica into a hydrochloric acid solution with a mass concentration of 5-20% according to a solid-liquid ratio of 1:3, the reaction temperature is 60 degrees, and the reaction time is 1 hour.
[0017] By adopting the above technical solution, after acid pretreatment, the mica surface becomes cleaner and the surface impurities are reduced, which helps to improve the uniformity and firmness of the titanium dioxide coating on the mica surface. The lattice structure of the mica surface will change in an acidic environment and under heating conditions. The hydrogen ions in the hydrochloric acid can exchange with some metal ions on the mica surface, and may also break the relatively stable chemical bonds on the mica surface, exposing more active sites.
[0018] Optionally, the surface of the titanium dioxide-coated mica is also coated with microencapsulated purslane extract.
[0019] Optionally, the specific steps of coating the microencapsulated purslane extract on the surface of the titanium dioxide-coated mica are: Add 50-60 parts of gelatin and 10-30 parts of purslane extract by weight to 100 parts of water, stir and dissolve at a constant temperature of 50-60°C to obtain solution A, add 40-50 parts of gum arabic and 1-3 parts of Tween to 100 parts of water, stir and dissolve at a constant temperature of 50-60°C to obtain solution B, and mix solution A with the solution to form a uniform emulsion; Use dilute hydrochloric acid solution to drop into the emulsion, adjust the pH value to 4.0-4.5, and continue stirring to carry out complex coagulation reaction; After the complex coagulation reaction is completed, the titanium dioxide coated mica is added to the emulsion and ultrasonically dispersed. After completion, 5-10 parts of a 1-3% calcium chloride solution are added dropwise to the reaction system, and stirring is continued during the addition process to obtain a microcapsule solution; The microcapsule liquid is separated by centrifugation to obtain a microcapsule precipitate, which is then washed and dried.
[0020] By adopting the above technical solution, the purslane extract has a significant anti-inflammatory effect and has a good alleviating effect on skin inflammation caused by ultraviolet radiation and other factors in children. After being microencapsulated, it is coated on the surface of titanium dioxide coated mica, so that when using sunscreen products, the purslane extract can act more accurately on children's skin and specifically reduce skin inflammation. The microencapsulated purslane extract is combined with the titanium dioxide coated mica, making the combination between the two more compact and stable.
[0021] In summary, this application has the following beneficial effects: 1. This application aims to solve the potential safety hazard of nanomaterials in traditional children's sunscreens that may penetrate children's skin barriers. By coating titanium dioxide on mica to form larger particles, the potential risks of nanoparticles are avoided and it is suitable for children. Mica is stable and mild in nature. During preparation, the reaction conditions and washing steps are strictly controlled to ensure that the product has appropriate pH and reduce irritation to children's skin. Reflux reaction for 2 hours under specific pH and temperature conditions can ensure uniform coating of titanium dioxide, improve product quality and performance, and the ultraviolet reflection and scattering ability of titanium dioxide can provide effective ultraviolet protection for children.
[0022] 2. Sodium alginate is preferably used in this application. Sodium alginate is a polysaccharide with rich functional groups (such as carboxyl and hydroxyl groups), which can bind to the mica surface through interactions such as hydrogen bonds. When titanium dioxide is added later, sodium alginate acts as a bridge between mica and titanium dioxide. It can guide titanium dioxide to be more evenly distributed on the mica surface, making the titanium dioxide coating more uniform and firm.
[0023] 3. In the present application, it is preferred to prepare a solution A containing gelatin and purslane extract and a solution B containing gum arabic and Tween respectively, mix the two to form an emulsion, add dilute hydrochloric acid to adjust the pH value for complex coagulation reaction, add titanium dioxide coated mica after the reaction is completed and ultrasonically disperse, then add calcium chloride solution, and finally centrifuge, wash and dry to obtain microcapsule precipitate. Through this technical solution, the anti-inflammatory effect of purslane extract is utilized, and after microencapsulation, it is coated on the surface of titanium dioxide coated mica, which can act more accurately on the skin when children use sunscreen products, reduce the inflammatory response caused by ultraviolet radiation, and make the combination of the two more tightly and stably. DETAILED DESCRIPTION
[0024] The present application is further described in detail below in conjunction with the examples. It is particularly noted that if no specific conditions are specified in the following examples, the experiments are carried out according to conventional conditions or the conditions recommended by the manufacturer. Unless otherwise specified, the raw materials used in the following examples can be obtained from common commercial sources. Example
[0025] Example 1 A method for coating titanium dioxide on mica: 35 g of rutile titanium dioxide with a particle size distribution of 30-200 nm and 65 g of 20 micron-sized sericite were mixed in a beaker, and 1100 g of deionized water was added, and the mixture was stirred at a speed of 800 r / min for 15 min to obtain a mixed solution; Add 5% by mass dilute hydrochloric acid solution to the mixed solution to adjust the pH of the mixed solution to 2-2.5; heat the mixed solution to 60°C by water bath and reflux for 2h; After the reaction is completed, stop heating, cool the mixture to room temperature, filter it through a filter, and then wash the filtered product with deionized water until the pH is 5-7; The washed product is placed in an oven and dried at 95° C. to obtain mica with titanium dioxide coated on the surface.
[0026] Example 2 A method for coating titanium dioxide on mica: 30 g of rutile titanium dioxide with a particle size of 30-200 nm and 70 g of sericite with a particle size of 20 microns were mixed in a beaker, and 1100 g of deionized water was added, and the mixture was stirred at a speed of 800 r / min for 15 min to obtain a mixed solution; Add 5% by mass dilute hydrochloric acid solution to the mixed solution to adjust the pH of the mixed solution to 2-2.5; heat the mixed solution to 60°C by water bath and reflux for 2h; After the reaction is completed, stop heating, cool the mixture to room temperature, filter it through a filter, and then wash the filtered product with deionized water until the pH is 5-7; The washed product is placed in an oven and dried at 95° C. to obtain mica with titanium dioxide coated on the surface.
[0027] Example 3 A method for coating titanium dioxide on mica: 40 g of rutile titanium dioxide with a particle size of 30-200 nm and 60 g of sericite with a particle size of 20 microns were mixed in a beaker, and 1100 g of deionized water was added, and the mixture was stirred at a speed of 800 r / min for 15 min to obtain a mixed solution; Add 5% by mass dilute hydrochloric acid solution to the mixed solution to adjust the pH of the mixed solution to 2-2.5; heat the mixed solution to 60°C by water bath and reflux for 2h; After the reaction is completed, stop heating, cool the mixture to room temperature, filter it through a filter, and then wash the filtered product with deionized water until the pH is 5-7; The washed product is placed in an oven and dried at 95° C. to obtain mica with titanium dioxide coated on the surface.
[0028] Example 4 65 g of 20 micron-sized sericite mica was placed in a beaker, and 1100 g of deionized water was added, and the mixture was stirred at a speed of 800 r / min to obtain a suspension, 25 g of sodium alginate (purity> 98%) was added to the suspension, the stirring speed was adjusted to 300 r / min, and the mixture was stirred for 10 min, and 35 g of rutile titanium dioxide with a particle size distribution of 30-200 nm was added to the suspension, and the mixture was stirred for 15 min to obtain a mixed solution; Add 5% by mass dilute hydrochloric acid solution to the mixed solution to adjust the pH of the mixed solution to 2-2.5; heat the mixed solution to 60°C by water bath and reflux for 2h; After the reaction is completed, stop heating, cool the mixture to room temperature, filter it through a filter, and then wash the filtered product with deionized water until the pH is 5-7; The washed product is placed in an oven and dried at 95° C. to obtain mica with titanium dioxide coated on the surface.
[0029] Example 5 A method for coating titanium dioxide on mica: The difference from Example 4 is that 20 g of sodium alginate is added to the suspension.
[0030] Example 6 A method for coating titanium dioxide on mica: The difference from Example 4 is that 30 g of sodium alginate is added to the suspension.
[0031] Example 7 A method for coating titanium dioxide on mica: The difference from Example 1 is that the titanium dioxide is anatase titanium dioxide.
[0032] Example 8 A method for coating titanium dioxide on mica: The difference from Example 1 is that the mica is muscovite.
[0033] Example 9 A method for coating titanium dioxide on mica: The difference from Example 1 is that the mica is synthetic fluorphlogopite.
[0034] Example 10 A method for coating titanium dioxide on mica: The difference from Example 1 is that the particle size of titanium dioxide is 10-30 nm.
[0035] Embodiment 11 A method for coating titanium dioxide on mica: The difference from Example 1 is that the particle size of titanium dioxide is 200-300 nm.
[0036] Example 12 A method for coating titanium dioxide on mica: The difference from Example 1 is that the mica needs to be acidified before being added to the beaker: Mica was added in a solid-liquid ratio of 1:3, the reaction temperature was 60 degrees, and the reaction time was 1 hour.
[0037] Example 13 A method for coating titanium dioxide on mica: The difference from Example 12 is that the mass concentration of the hydrochloric acid solution is 5%.
[0038] Embodiment 14 A method for coating titanium dioxide on mica: The difference from Example 12 is that the mass concentration of the hydrochloric acid solution is 20%.
[0039] Embodiment 15 A method for coating titanium dioxide on mica: The difference from Example 1 is that the obtained mica with the surface coated with titanium dioxide is further subjected to the following treatment: 55 g of gelatin and 20 g of purslane extract were added to 100 g of deionized water, heated in a water bath at 55° C., and stirred to dissolve to obtain solution A. 45 g of gum arabic and 2 g of Tween-10 were added to 100 g of deionized water, heated in a water bath at 55° C., and stirred to dissolve to obtain solution B. Solution A was mixed with the solution to form a uniform emulsion. Use a 5% mass fraction of dilute hydrochloric acid solution to drop into the emulsion, stir while adding, adjust the pH value to 4.0-4.5, and continue stirring to carry out complex coagulation reaction. React for 2h; After the complex coacervation reaction was completed, 100 g of the solution was added to the emulsion, and ultrasonic dispersion was performed at 48 kHz for 5 minutes. After the dispersion was completed, 8 g of a 2% calcium chloride solution was added dropwise to the reaction system, and stirring was continued during the addition to obtain a microcapsule solution. The microcapsule liquid is separated by centrifugation to obtain a microcapsule precipitate, which is then washed and dried.
[0040] Example 16 A method for coating titanium dioxide on mica: The difference from Example 16 is that 55g of gelatin and 10g of purslane extract are added to 100g of deionized water, heated at a constant temperature of 55°C in a water bath, and dissolved by stirring to obtain solution A.
[0041] Embodiment 17 A method for coating titanium dioxide on mica: The difference from Example 16 is that 55 g of gelatin and 30 g of purslane extract are added to 100 g of deionized water, heated at a constant temperature of 55° C. in a water bath, and dissolved by stirring to obtain solution A.
[0042] Comparative Example Comparative Example 1 A method for coating titanium dioxide on mica: 40 g of rutile titanium dioxide with a particle size of 30-200 nm and 60 g of sericite with a particle size of 20 microns were mixed in a beaker, and 1100 g of deionized water was added, and stirred to obtain a mixed solution; The temperature of the mixed solution was raised to 60°C by heating in a water bath, and refluxed for 2 hours; after the reaction was completed, the heating was stopped, the mixed solution was cooled to room temperature, filtered through a filter, and the filtered product was washed with deionized water until the pH was 5-7; The washed product was placed in an oven and dried at 95°C.
[0043] Comparative Example 2 A method for coating titanium dioxide on mica: The difference from Example 4 is that 15 g of sodium alginate is added to the suspension.
[0044] Comparative Example 3 A method for coating titanium dioxide on mica: The difference from Example 4 is that 35 g of sodium alginate is added to the suspension.
[0045] Comparative Example 4 A method for coating titanium dioxide on mica: The difference from Example 13 is that 55 g of gelatin and 5 g of purslane extract are added to 100 g of deionized water, heated at a constant temperature of 55° C. in a water bath, and dissolved by stirring to obtain solution A.
[0046] Comparative Example 5 A method for coating titanium dioxide on mica: The difference from Example 13 is that 55 g of gelatin and 35 g of purslane extract are added to 100 g of deionized water, heated at a constant temperature of 55° C. in a water bath, and dissolved by stirring to obtain solution A.
[0047] Performance testing Detection Methods Take 5g of the titanium dioxide-coated mica prepared above, mix it with 10g of glycerol, and apply it on the surface of a glass substrate with a transmittance greater than 99%. The coating area is the same. Place a UVB lamp on one side of the glass substrate for irradiation, test the ultraviolet intensity on the other side of the glass substrate, and calculate the intensity difference to find the ultraviolet isolation rate.
[0048] 5 g of the titanium dioxide-coated mica prepared as above was taken for fluorescent staining and mixed with 10 g of glycerol as a sample. Three-month-old hairless mice from Jiankang were selected and 2 g of the sample was applied on the body surface of the mice. The application was repeated at the same position every 24 hours for 30 days. After the application, the epidermis of the mice, including the epidermis, dermis and subcutaneous tissue, was taken to observe whether the titanium dioxide in the titanium dioxide-coated mica penetrated into the dermis or subcutaneous tissue.
[0049] 5 g of the titanium dioxide-coated mica prepared above was taken and mixed with 10 g of glycerol as a sample, and applied to the same area of the arm of a volunteer who had no skin disease. 3 g was applied each time, once every 24 hours, and repeated five times. The applied area was observed for allergic and inflammatory symptoms, and the bacteria on the skin surface were tested before and 24 hours after application, and the antibacterial rate was calculated.
[0050] Table 1 Experimental data statistics Combining Example 1 and Comparative Example 1 with Table 1, it can be seen that during the preparation process, by strictly controlling the reaction conditions and washing steps, the pH of the final product is ensured to be within a range suitable for children's skin, thereby reducing irritation to children's skin. The pH of the mixed solution is adjusted to 2-2.5 by dripping a dilute hydrochloric acid solution, and the temperature of the mixed solution is raised to 45-80° C. for reflux reaction for 2 hours, which can ensure uniform coating of titanium dioxide on the mica surface and improve the quality and performance of the product.
[0051] Combining Examples 4-6 and Comparative Examples 2-3 and Table 1, it can be seen that 25g, 20g, and 30g of sodium alginate were used in Examples 4-6 to participate in the process of coating titanium dioxide on mica, Comparative Example 2 used 15g of sodium alginate, and Comparative Example 3 used 35g of sodium alginate. From the perspective of ultraviolet isolation rate, Examples 4-6 show a good ultraviolet isolation effect as a whole, and the data are relatively close. Sodium alginate helps to improve the ultraviolet isolation ability of the product. Comparing Comparative Examples 2 and Comparative Examples 3 with Example 4-6, when the amount of sodium alginate is too small, it cannot fully play its role in guiding titanium dioxide to uniformly coat the surface of mica, making the ultraviolet isolation rate slightly lower; and although the amount is too much, the ultraviolet isolation rate is not significantly reduced, and the effect of continuing to increase the amount will not be significantly improved, which is not conducive to cost control. On the whole, the amount of sodium alginate used in this application is about 20-30g, which is more beneficial to the improvement of comprehensive properties such as coating effect, ultraviolet isolation rate and antibacterial rate.
[0052] Combining Examples 16-18 and Comparative Examples 4-5 and Table 1, it can be seen that the amounts of purslane extract in Examples 16-18 are 20g, 10g, and 30g, respectively, while Comparative Examples 4 and 5 use 5g and 35g of purslane extract. Judging from the data on ultraviolet light isolation rate, the amount of purslane extract has a relatively limited effect on ultraviolet light isolation. However, from the perspective of antibacterial rate, Examples 16-18 show a trend that the antibacterial rate changes as the amount of purslane extract increases. In summary, the amount of purslane extract needs to be controlled in the range of 20-30g, which can better exert its antibacterial properties on the basis of ensuring the basic sunscreen function of the product.
[0053] It can be seen from Examples 1-3 and Table 1 that conventional sunscreens use a large amount of nanomaterials, which may cause safety hazards that nanoparticles may penetrate children's skin barriers and enter the human body. The present application scheme forms relatively large particles by coating mica with titanium dioxide, which does not generate potential risks of nanoparticles and is particularly suitable for children. Titanium dioxide has excellent ultraviolet reflection and scattering capabilities. By coating mica with titanium dioxide, the sunscreen effect of titanium dioxide can be fully exerted to provide effective ultraviolet protection for children.
[0054] Combining Example 1 and Examples 4-6 with Table 1, it can be seen that Example 1 does not add sodium alginate, and Examples 4-6 add different amounts of sodium alginate. In terms of ultraviolet light isolation rate, the overall ultraviolet light isolation rate of Examples 4-6 is higher than that of Example 1, indicating that the addition of sodium alginate helps to improve the product's ability to isolate ultraviolet light. This is because sodium alginate can make titanium dioxide more evenly and firmly coated on the mica surface, and better play the ultraviolet light reflection and scattering effect of titanium dioxide. From the perspective of antibacterial rate, the antibacterial rate of Examples 4-6 is also higher than that of Example 1, indicating that the addition of sodium alginate has a positive effect on improving the antibacterial properties of the product.
[0055] It can be seen from Example 1 and Examples 7-11 and Table 1 that the titanium dioxide particle size of 30-200 nm has the best comprehensive effect. In the present application, the mica can be sericite, muscovite, or synthetic fluorphlogopite, and the titanium dioxide can be rutile or anatase, all of which can achieve good anti-ultraviolet effects and are safe and non-irritating.
[0056] Combining Example 1 and Examples 12-14 with Table 1, it can be seen that Example 1 did not perform acid pretreatment on mica. From the perspective of ultraviolet light shielding rate, the ultraviolet light shielding rates of Examples 12-14 are better than those of Example 1 as a whole, indicating that after the mica is pretreated by acid, the surface is clean and the surface active sites are increased, so that the coating effect of titanium dioxide on the mica is better, thereby improving the sun protection ability of the product.
[0057] Combining Example 1 and Examples 15-17 and Table 1, it can be seen that Examples 15-17 carried out subsequent treatment related to microcapsules and adjusted the amount of purslane extract. From the perspective of ultraviolet light isolation rate, Examples 15-17 are somewhat different from Example 1, but this difference is relatively not particularly large, indicating that subsequent microcapsule treatment and other operations do not have a dominant effect on the main sunscreen performance of the product, such as ultraviolet light isolation, but there is also a certain regulatory effect. However, in terms of antibacterial rate, the antibacterial rate of Examples 15-17 is significantly improved compared to Example 1, indicating that purslane extract has a significant optimization effect on the antibacterial performance of the product. By forming a microcapsule structure and the synergistic effect between the various components, it can effectively inhibit the growth of microorganisms and enhance the antibacterial ability of the product, so that the product can show better application effects in terms of antibacterial while having sunscreen function.
[0058] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.
Claims
1. A method for coating mica with titanium dioxide, characterized in that: The following steps are involved: Add 60-70 parts of mica by weight to 1000-1200 parts of water, stir to form a suspension, then add 30-40 parts of titanium dioxide to the suspension and stir to obtain a mixed solution; Add dilute hydrochloric acid solution to the mixed solution to adjust the pH of the mixed solution to 2-2.5; raise the temperature of the mixed solution to 45-80°C and reflux for 2h; After the reaction is completed, the mixed solution is cooled to room temperature, filtered and washed until the pH is 5-7; The washed product is placed in an oven for drying to obtain mica with titanium dioxide coated on the surface.
2. The method for coating mica with titanium dioxide according to claim 1, characterized in that: The following steps are also included: Add 60-70 parts of mica by weight to 1000-1200 parts of water, stir to form a suspension, add 20-30 parts of sodium alginate to the suspension, stir for 10-15 minutes, then add 30-40 parts of titanium dioxide to the suspension and stir for 10-15 minutes to obtain a mixed solution; Add dilute hydrochloric acid solution to the mixed solution to adjust the pH of the mixed solution to 2-2.5; raise the temperature of the mixed solution to 45-80°C and reflux for 2h; After the reaction is completed, the mixed solution is cooled to room temperature, filtered and washed until the pH is 5-7; The washed product is placed in an oven for drying to obtain mica with titanium dioxide coated on the surface.
3. The method for coating titanium dioxide on mica according to claim 1 or 2, characterized in that: The mica includes one of sericite, muscovite and synthetic fluorphlogopite.
4. The method for coating titanium dioxide on mica according to claim 1 or 2, characterized in that: The titanium dioxide includes one of rutile titanium dioxide and anatase titanium dioxide.
5. The method for coating titanium dioxide on mica according to claim 1 or 2, characterized in that: The particle size of the titanium dioxide is 30-200 nm.
6. The method for coating titanium dioxide on mica according to claim 1 or 2, characterized in that: The mica is also subjected to acidification pretreatment before preparing the suspension, and the acidification pretreatment comprises: Add mica into a hydrochloric acid solution with a mass concentration of 5-20% at a solid-liquid ratio of 1:3, the reaction temperature is 60 degrees, and the reaction time is 1 hour.
7. The method for coating titanium dioxide on mica according to claim 1 or 2, characterized in that: The surface of the mica coated with titanium dioxide is also coated with microencapsulated purslane extract.
8. The method for coating titanium dioxide on mica according to claim 7, characterized in that: The specific steps of preparing the mica-coated microencapsulated purslane extract with titanium dioxide coated on the surface are as follows: Add 50-60 parts of gelatin and 10-30 parts of purslane extract by weight to 100 parts of water, stir and dissolve at a constant temperature of 50-60°C to obtain solution A, add 40-50 parts of gum arabic and 1-3 parts of Tween to 100 parts of water, stir and dissolve at a constant temperature of 50-60°C to obtain solution B, and mix solution A with the solution to form an emulsion; Use dilute hydrochloric acid solution to drop into the emulsion, adjust the pH value to 4.0-4.5, and continue stirring to carry out complex coagulation reaction; After the complex coagulation reaction is completed, the titanium dioxide-coated mica is added to the emulsion and ultrasonically dispersed. After completion, 5-10 parts of a 1-3% calcium chloride solution are added dropwise to the reaction system, and stirring is continued during the addition process to obtain a microcapsule solution; The microcapsule liquid is separated by centrifugation to obtain a microcapsule precipitate, which is then washed and dried.
Citation Information
Cited By
Method for coating mica with titanium dioxide
WO2026137981A1